Dissimilar tumor cell populations in ascitic fluid of ovarian cancer patients - E. V. Kaigorodova; N. V. Fedulova; M. O. Ochirov; D. A. Dyakov; S. V. Molchanov; N. Yu. Chasovskikh (Бюллетень сибирской медицины)
Ovarian cancer is one of the most aggressive and hard-to-treat cancers. About 75% of ovarian cancer cases are detected at later stages of the disease. Ascitic fluid is promising biological material to get information about the tumor nature in ovarian cancer. Peritoneal dissemination is one of the most unfavorable factors of malignant tumor progression. However, prognostic factors associated with malignant ascites are not well understood.The aim of the study was to evaluate various tumor cell populations in ascitic fluid of ovarian cancer patients by laser multicolor flow cytometry using a molecular panel of EpCam, CD45, CD44, CD24, CD133, and N-cadherin markers. The prospective study included 16 patients aged 36 to 76 years with newly diagnosed FIGO stage Ic–IV ovarian cancer, who were admitted for treatment to the CancerResearch Institute of Tomsk National Research Medical Center. The study material included EDTAstabilized ascitic fluid sampled during laparoscopy. Various populations of ascitic tumor cells (with stemness features, with epithelial mesenchymal transition (EMT) features, without stemness and EMT features, with a combination of these features, as well as atypical / hybrid cell populations) were identified by multicolor flow cytometry on a BDFACSCanto apparatus (USA) using fluorochrome-labeled EpCam, CD45, CD44, CD24, CD133, and N-cadherin monoclonal antibodies and the BD FACSDiva software. The study revealed twelve populations of Epcam-positive cells in ascitic fluid of ovarian cancer patients. The cell composition of ascitic fluid in ovarian cancer patients is represented by a heterogeneous population. A large fraction of ascitic tumor cells are atypical / hybrid tumor cells with stemness features as well as Epcam+CD45–CD44+CD24+CD133+/-cancer stem cells, both with and without EMT features.